Vigilant Keratinocytes Trigger Pathogen-Associated Molecular Pattern Signaling in Response to Streptococcal M1 Protein - Persson, Sandra T. (Infect Immun, 2015)
The human skin exerts many functions in order to maintain its barrier integrity and protect the host from invading microorganisms. One such pathogen is Streptococcus pyogenes, which can cause a variety of superficial skin wounds that may eventually progress into invasive deep soft tissue infections. Here we show that keratinocytes recognize soluble M1 protein, a streptococcal virulence factor, as a pathogen-associated molecular pattern to release alarming inflammatory responses. We found that this interaction initiates an inflammatory intracellular signaling cascade involving the activation of the mitogen-activated protein kinases extracellular signal-regulated kinase (ERK), p38, and Jun N-terminal protein kinase and the subsequent induction and mobilization of the transcription factors NF-κB and AP-1. We also determined the imprint of the inflammatory mediators released, such as interleukin-8 (IL-8), growth-related oncogene alpha, migration inhibitory factor, extracellular matrix metalloproteinase inducer, IL-1α, IL-1 receptor a, and ST2, in response to streptococcal M1 protein. The expression of IL-8 is dependent on Toll-like receptor 2 activity and subsequent activation of the mitogen-activated protein kinases ERK and p38. Notably, this signaling seems to be distinct for IL-8 release, and it is not shared with the other inflammatory mediators. We conclude that keratinocytes participate in a proinflammatory manner in streptococcal pattern recognition and that expression of the chemoattractant IL-8 by keratinocytes constitutes an important protective mechanism against streptococcal M1 protein.